ECONOMIC INEQUALITY AND POLITICAL RIGHTS IN RAWLS’ THEORY OF JUSTICE: AN ANALYSIS FROM THOMAS SCANLON (Revista Direito em Debate, 2021)
The present article intends to problematize the way the issue of how socioeconomic inequalities and political rights are dealt with in the theory of justice originally formulated by John Rawls. It is well known that Rawls, in the decade of 1970, performed a revolution in the debates about distributive justice with the formulation of the theory that became known as justice as fairness, which is based in the proposition of two principles of justice, the first having priority over the second, in order to rule society’s basic structure. Very recently, however, a set of theoretical challenges to the liberal egalitarian tradition, to which Rawls is a major figure, was presented by Thomas Scanlon, in his proposal of attributing equality an intrinsic value. The aim of this work is to show how one of the issues raised by Scanlon, concerning political participation, can be capable of seriously compromising Rawls’s original proposal, in a way that the distribution prescribed by the principles themselves would break the priority between them. Firstly, we shall make a systematic study of how Rawls elaborates his two principles of justice and what is the place of equality within them, emphasizing the relevant elements to the subsequent analysis. Then, we shall try to demonstrate, starting from the point of view offered by Scanlon, how it is possible to find in Rawls a tension between the guarantee of a right to equal political participation to all, on the one hand, and the permission to socioeconomic inequalities, on the other.
Keywords: Justice. Inequality. Participation.